Controlled potential electrodeposition and characterization of ZNTE thin films on indium tin oxides - Al-Bat’hi Mohamad, Souad; Basirun, W. J.; Ibrahim, Z. A.; Arof, A. K. (2009)
Electrodeposition of ZnTe thin films by controlled potential method from aqueous solutions on ITO were done to investigate characteristics suitable as a window material in solar cells technology. The influence of bath temperature and deposition potential towards the Zn:Se ratio and the crystallinity are discussed. The electrodeposited films were investigated by using X-Ray Diffraction, Energy Dispersive Analysis of x-ray, Scanning Electron Microscopy and UV spectroscopy. Optical measurements were done on these samples and show a good agreement with reported results.